Knee Joint Troubles in Tea Pickers - TORII, Suguru; KUNOGI, Jun-ichi; KATSUMOTO, Hiromu; YOSHIKAWA, Yukio; HARADA, Rikizo; SUYAMA, Tetsuo; SHIMOJO, Hitoshi; SATO, Ikuo; KODAMA, Misuzu (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1986)
Investigation was made into knee joint problems among tea pickers through a questionnaire. Following this, physical examinations were given and radiography was taken. Of the male respondents, 18.9% said that they have pains in the knee (s). The corresponding figure for the women was a high as 38.5%. The number of men and women who complained of knee pain increased with age. However, it was not clear whether the incidence of knee pain has any bearing on the number of years they had worked or working hours per day. Rather, it seems to depend on the configuration of the plantation. Knee pain occurs more frequently in persons working on sloping and hilly lands than those working on flat land. The difference in Q-angle is wider in the hilly area than in the flat land. X-ray examination of the knee joint of the persons who complained of sensations revealed degenerative changes in the form of the synovial cavity. Changes in the form of the patella were more evident in the persons working on the sloping land than on the flat land. On the slope, tea pickers have to bend their knees, requring femoral quadriceps and crural triceps to maintain contraction for cours. Thus the level of stress on the kneecaps becomes high. To prevent knee joint injuries, improvement of footings, mechanization of collecting work, decreases in the frequency of decending and ascending the slop, and having a rest at proper intervals are necessary. Furthermore, it is necessary to strengthen femoral quadriceps by excercise and control weight.